Analisis Faktor Keberhasilan Pengobatan Tuberkulosis Paru di Kecamatan Mojoroto Kota Kediri Tahun 2022 dengan Regresi Logistik - Windha Ayu Pramesti; Mohamad Anis Fahmi (Ficco Scientific Corner, 2024)
Background: Treatment success is an effort to control and manage TB patients through indicators of treatment program success rates to assess the progress of TB control. Kediri City has Mojoroto Sub-district which has the lowest average percentage of TB treatment success with only 81.54%. This study uses binary logistic regression analysis to determine the factors that can influence the success of Lung TB treatment in Mojoroto District, Kediri City in 2022. Methods: This study uses an observational research design, analyzing secondary data obtained from the Kediri Regency Health Office, using Quantum GIS software. Data was collected from health reports and mapped to visualize the distribution of doctors who have completed their credentialing across the health centers. Results: The results of hypothesis testing using Fisher's Exact Test for the bivariate test, obtained the results that the variable of drug compliance (p value= 0.00 < 0.05) influences the success of Lung TB treatment. Meanwhile, the variables of age (p = 0.246 > 0.05), family support (p value= 1.000 > 0.05) and comorbidities (p value= 0.360 > 0.05) do not influence the success of Lung TB treatment. In addition, the results of multivariate analysis with binary logistic regression test obtained results from the simultaneous test that there is at least 1 variable that affects the success of Lung TB treatment and partial test showed that none of them affect the success of Lung TB treatment. Conclusions: It is recommended to approach cadres as supervisors of swallowing medicine, taking medicine on time without leaving medicine, and being confident that they can recover and complete the recording on the treatment card as an archive that can facilitate program evaluation.